2018
DOI: 10.1128/aac.01150-18
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem Combined with Ciprofloxacin Combats Hypermutable Pseudomonas aeruginosa from Respiratory Infections of Cystic Fibrosis Patients

Abstract: Hypermutable organisms are prevalent in chronic respiratory infections and have been associated with reduced lung function in cystic fibrosis (CF); these isolates can become resistant to all antibiotics in monotherapy. This study aimed to evaluate the time course of bacterial killing and resistance of meropenem and ciprofloxacin in combination against hypermutable and nonhypermutable Static concentration time-kill experiments over 72 h assessed meropenem and ciprofloxacin in mono- and combination therapies aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 68 publications
2
30
0
Order By: Relevance
“…The synergy was concluded to arise from enhanced penetration of the β‐lactam to its molecular target site as a result of outer membrane disruption by the aminoglycosides. A PD DDI model, based on the in vitro evaluation of bacterial killing using a hollow‐fiber infection model system, was translated in vivo to a murine thigh infection model and to patients simply by integrating the PK models of the antibiotics in those species. Simulations with the PK/PD model suggested that the continuous infusion of a high‐dose β‐lactam combined with an aminoglycoside would constitute a promising regimen for optimal bacterial killing without regrowth.…”
Section: Quantification Methods For Pd Ddismentioning
confidence: 99%
“…The synergy was concluded to arise from enhanced penetration of the β‐lactam to its molecular target site as a result of outer membrane disruption by the aminoglycosides. A PD DDI model, based on the in vitro evaluation of bacterial killing using a hollow‐fiber infection model system, was translated in vivo to a murine thigh infection model and to patients simply by integrating the PK models of the antibiotics in those species. Simulations with the PK/PD model suggested that the continuous infusion of a high‐dose β‐lactam combined with an aminoglycoside would constitute a promising regimen for optimal bacterial killing without regrowth.…”
Section: Quantification Methods For Pd Ddismentioning
confidence: 99%
“…Serial samples were collected at 5 to 10 min predose (0 h) and at 1.5, 5, 24, 29, and 48 h. The bacterial suspensions were centrifuged at 24 h, the supernatant carefully removed, and bacteria resuspended in fresh, prewarmed medium that contained the targeted antibiotic concentration(s). As previously described, supplemental meropenem doses corresponding to 30% of the original dose were added at 6 and 30 h to further offset the known thermal degradation of meropenem (52,67). The samples for viable counting were washed twice in sterile saline, and counts determined by manually plating 100 l of undiluted or appropriately diluted suspension in saline onto agar plates.…”
Section: Methodsmentioning
confidence: 99%
“…The first-order growth rate constant (k12,IR) was defined as 60/MGT IR , with MGT IR denoting the mean generation time for the bacterial population. We used a direct killing process [25,26,27] for both tobramycin and ciprofloxacin. The KC 50,TOB and KC 50,CIP were the tobramycin and ciprofloxacin concentrations required to achieve 50% of the maximum killing rate constant ( K max ).…”
Section: Methodsmentioning
confidence: 99%